A new semi-orthotopic bone defect model for cell and biomaterial testing in regenerative medicine. (December 2021) - Andrés Sastre, E.; Nossin, Y.; Jansen, I.; Kops, N.; Intini, C.; Witte-Bouma, J.; van Rietbergen, B.; Hofmann, S.; Ridwan, Y.; Gleeson, J.P.; O'Brien, F.J.; Wolvius, E.B.; et al.
Abstract: In recent decades, an increasing number of tissue engineered bone grafts have been developed. However, expensive and laborious screenings in vivo are necessary to assess the safety and efficacy of their formulations. Rodents are the first choice for initial in vivo screens but their size limits the dimensions and number of the bone grafts that can be tested in orthotopic locations. Here, we report the development of a refined murine subcutaneous model for semi-orthotopic bone formation that allows the testing of up to four grafts per mouse one order of magnitude greater in volume than currently possible in mice. Crucially, these defects are also "critical size" and unable to heal within the timeframe of the study without intervention. The model is based on four bovine bone implants, ring-shaped, where the bone healing potential of distinct grafts can be evaluated in vivo . In this study we demonstrate that promotion and prevention of ossification can be assessed in our model. For this, we used a semi-automatic algorithm for longitudinal micro-CT image registration followed by histological analyses. Taken together, our data supports that this model is suitable as a platform for the real-time screening of bone formation, and provides the possibility to study bone resorption, osseointegration and vascularisation. Graphical abstract: Image 1